Psoriatic arthritis imaging: a review of scoring methods. (11th February 2005) - van der Heijde, D; Sharp, J; Wassenberg, S; Gladman, D D
Abstract : Structural damage assessed on conventional radiographs is an important outcome measure in psoriatic arthritis. This article reviews the available scoring methods. A full description of the methods is given as well as information on various aspects of validity.